Perish : a novel - Watkins, LaToya (Tiny Reparations Books, an imprint of Penguin Random House LLC, 2022)
"LaToya Watkins's Perish follows four members of the Turner clan: Julie B., a woman who regrets her wasted youth and the time spent under Helen Jean's thumb; Alex, a police officer grappling with a dark and twisted past; Jan, mother of two, who yearns to go to school and leave Jerusalem and all of its trauma behind for good; And Lydia, a woman whose marriage is falling apart because her body can't seem to stay pregnant; as they're called home to say goodbye to their mother and grandmother, Helen Jean. Told through alternating chapters, and set in a vividly drawn, tight-knit rural, Black Texan community, Perish explores the effects of inherited trauma and intra-generational violence and pain as the family's "reunion" unearths long-kept secrets and forces each member to ask themselves important questions about who is deserving of forgiveness and who bears the cross of blame. With powerful, sharp prose and a sense of place that is wholly immersive, offering a nuanced look into black communites in Texas, this beautiful yet heart-wrenching debut novel will pull you in and drop you into the world LaToya has masterfully crafted within the pages"--